Escoamento de materiais viscoplásticos: Dam Break Flow - Modolo, Alan Victor Ferreira (2017)
Over the last century, many authors have studied the Dam Break Flow. The understanding of this type of phenomenon is of great relevance,since it involves applications in dams that offer multiple benefits for humanity. However, the rupture of one of these dams may have undesirable and immeasurable consequences for society and the mining sector, for example.In this work we are interested in understanding how the Froude number and the non-Newtonian properties, particularly the viscoplasticity, affect the flow profile and the distance reached by the material after the Dam Break Flow. Such results are compared with the displacement of a Newtonian fluid. Through a simple experimental approach, a solution of viscoplastic or Newtonian material initially stored in a reservoir is released immediately. Such results are compared with the displacement of a Newtonian fluid. The flow images are captured during the test in two different ways. One is made using a CCD camera and the other is through Particle Image Velocimetry. From the images obtained by the CCD camera, a flow map is obtained, with their respective velocities, liquid level, air-liquid interface format and distance traveled by the material. The results obtained with the PIV are to determine the velocity field of the initial moments of the Dam Break Flow, for the different types of materials studied. In this work, it is shown that the plasticity of the material has total influence on the distance reached by the flow and also the results in instabilities along the flow. It has also been identified that the viscoplastic fluid reaches initial velocities greater thanthe Newtonian case. However, in the course of flow, they decrease rapidly. When the viscoplastic case is analyzed for a bed with roughness, it is observed that for a smooth surface, there is sliding of the material in a significant way for high values of plasticity. Through PIV analysis, it was found that the velocity of the wavefront is somewhat less than the maximum velocity obtained by the flow